Botanical Control of Late Blight of Potato - Maharjan, BL; Shreshta, K; Basnyat, S (Nepal Journal of Science and Technology, 2011)
Late blight caused by Phytophthora infestans (Mont.) De Bary is one of the most devastating diseases of potato. Although a large number of synthetic fungicides have been recommended to control this organism, most of them have proved to be pollutive, carcinogenic and the pathogen develops resistance quickly. Botanical control is one of the safe substitutes to be explored to control this phytopathogen. In the present study an attempt has been made to evaluate the antifungal activity of plant extracts against the above pathogen. Crude ethanolic extracts of five different plant materials viz. Brassica nigra, Cinnamomum camphora, Eupatorium adenophorum, Lantana camara and Melia azedarach were screened and tested against the fungal isolate of P. infestans. The antifungal activity of the crude extracts was evaluated by agar well diffusion method and two fold broth dilution method. The moisture content was highest in the twigs of L. camara and lowest in the cake of B. nigra. C. camphora gave the highest yield of 70% while M. azedarach had the lowest yield of (9.75%) of crude extracts. B. nigra was found most effective against P. infestans with both MIC and MFC values at 6.25mg/ml while C. camphora was found least effective. Different types of plant extracts with different concentrations significantly (P<0.05) inhibited the growth of the pathogen. The extracts used in this experiment were found to be suitable for the control of the pathogen. Key words: botanical control; antifungal; MIC; ZOI; MFC DOI: 10.3126/njst.v11i0.4087 Nepal Journal of Science and Technology 11 (2010) 37-40